Стадії юридичної відповідальності: загальнотеоретична характеристика - Калєніченко, Л. І.; Kalenichenko, L. I.; Калєніченко Лідія Іванівна (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 2 (77). - С. 19-26, 2017)
Проаналізовано основні стадії юридичної відповідальності як динамічного правового явища. Залежно від ступеня встановлення об’єктивної істини у справі виокремлено такі стадії юридичної відповідальності: 1) стадію виникнення підстав для притягнення до юридичної відповідальності; 2) стадію притягнення до юридичної відповідальності та її встановлення; 3) стадію настання юридичної відповідальності. Надано загальнотеоретичну характеристику виокремлених стадій.

It has been established that stages of legal liability as a dynamic legal phenomenon are relatively independent points in the mechanism of its imposition. It has been proved that depending on the degree of establishing the objective truth in the case by the main stages of legal liability are: 1) the stage of the genesis of reasons for bringing to legal liability; 2) the stage of bringing to legal liability and its establishment; 3) the stage of attachment of legal liability. General and theoretical characteristics of the allocated stages have been provided; it has been noted that each of them is characterized with the relevant points of the genesis of legal relations of the liability and the points of their termination.

Проанализированы основные стадии юридической ответственности как динамического правового явления. В зависимости от меры установления объективной истины по делу выделены такие стадии юридической ответственности: 1) стадия возникновения оснований для привлечения к юридической ответственности; 2) стадия привлечения к юридической ответственности и её установления; 3) стадия наступления юридической ответственности. Дана общетеоретическая характеристика выделеных стадий.
Stages of legal liability: general and theoretical characteristics
Стадии юридической ответственности: общетеоретическая характеристика
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; юридична відповідальність; стадії юридичної відповідальності; підстави для притягнення до юридичної відповідальності; притягнення до юридичної відповідальності; встановлення юридичної відповідальності; настання юридичної відповідальності; liability; legal liability; stages of legal liability; attachment of legal liability; юридическая ответственность; стадии юридической ответственности; привлечение к юридической ответственности